The Journey Of Searching The Identiy Of Audrina’s Character In My Sweet Audrina Novel By V.C Andrews - Kumkelo, Sofia; Maca, Sudirman; Abeng, Andi Tenri (Humaniora: Journal of Linguistics, Literature, and Education, 2024)
This study aimed to discover and explain the factors that influence the formation of identity search journey of the main character and types of psychology development and formation of identity in the novel My Sweet Audrina novel by V.C Andrews. The data sources used in this study is novel My Sweet Audrina novel by V.C Andrews. In analyzing the data, the writer used descriptive qualitative research method through psychological approach. Data were obtained by using the techniques of reading, noting, and analyzing. While in classifying the data, the writer used interpersonal theory by Sullivan. In this study, the writer analyzed the novel My Sweet Audrina novel by V.C Andrews in order to find the identity search by the main character. The results of this study indicate that there were 20 data that portrayed identity search that become the factors that influence the formation in the novel. There were 3 types of self formation from psychological development found from the data they were 5 Bad me, 3 Good me and 12 Not me. All of the three aspects above signficantly influenced the psychological of the main character and turned her into a strong character menatally and psychally